International Peace and Religion in Uzbekistan Tolerance Issues - Inoyatov Kutlug Hamdamovich (Peerian Journals Publishing, 2022)
According to the data, there are more than 1,600 nations on earth (3,000 in some sources) more than) their number ranges from a few tens of thousands to several hundred million. In terms of numbers, nations are divided into four groups. These include: a) the largest number of nations (Chinese more than 1 billion, - Indians, Americans, Russians, Japanese more than a hundred miles); b) a large number of nationalities (from 50 million to 100 million - the British, French, Spaniards, Turks, etc.); c) large nations (from 10 million to 50 million - Uzbeks, Portuguese, Poles, etc.); g) minorities (several tens of thousands to one million each). However, it should be noted that the number of nations cannot be the basis for their greatness or hegemony. Indeed, equality, freedom and liberty of all nations are one of the basic principles of the Universal Declaration of Human Rights and one of the basic principles of world politics
Keywords: number; principles; Universal; Declaration